Metode Problem Solving, Minat Belajar, dan Pengalaman Belajar terhadap Kemampuan Berpikir Kritis - Rokhman; Onik Farida Ni'matullah (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2020)
Problem solving learning model is a learning approach that presents problems as an initial foundation to build students' critical thinking skills by skillfully solving problems. The problem presented is a problem that has a context with the real world, so it is able to encourage students to think actively in accordance with the experiences they have experienced. Researchers chose Cluster II SDN Lumbang Subdistrict Pasuruan Regency as a place of research, because with the consideration that the school had never done research, especially social studies subjects. The purpose of this study is to find out: (1) The effect of problem solving learning methods on critical thinking skills, (2) The influence of learning interest on critical thinking skills, (3) The effect of learning experiences on critical thinking skills, and (4) The influence of problem solving learning methods, interest in learning, learning experiences on critical thinking skills. This type of research is quantitative research. Variables determining learning problem solving, learning interest, learning experiences, and critical thinking skills. The study population consisted of 158 students, while the sample was 113 students. Data collection techniques using questionnaires. The analysis technique used is multiple linear regression. The results showed that simultaneously and partially Problem Solving Learning Method, Learning Interest, Learning Experience affect Critical Thinking Ability